An optimization strategy for enhancing energy consumption performance in digital currency miner's building. Issue 2 (24th April 2023) - Akbarnavasi, Hossein; Ledari, Masoumeh Bararzadeh; Ghadertootoonchi, Alireza
Abstract: Cryptocurrencies, as a way of extraction, are categorized into two main groups of non‐mineable and mineable. Bitcoin (BTC), the most famous mineable digital currency, utilizes the Proof of Work (PoW) algorithm for maintaining network solidarity. Its mining process is done by devices known as application specific integrated circuits (ASICs), which consume electricity and turn it into heat. They shall operate within an accepted temperature range of around 25°C; otherwise, they will face an efficiency drop; consequently, all mining sites require a proper cooling system. This study aims to investigate the problem of high energy consumption for cooling in digital currency mining sites and to present a solution for that via optimizing the capacity and operation of the chiller and ice thermal storage system (ITS). The results show the utilization of the ITS system reduces the operational costs by 10%, and the ITS system provides 1320 kWh of cooling energy during peak hours. Finally, the sensitivity analysis results considering the impact of the electricity tariff on the size and operation of the system have confirmed that with an increase in peak time tariff, the role of the ITS system in cost reduction increases.